The Perception of Filipinos on the Advent of Cryptocurrency and Non-Fungible Token (NFT) Games - Francisco, Ryan D.; Rodelas, Nelson C.; Ubaldo, John Edison T. (International Journal of Computing Sciences Research, 2022)
Purpose – This study aims to shed light on the rise of play-to-earn games in the Philippines alongside cryptocurrency. The lack of research and public understanding of its benefits and drawbacks prompted the researchers to investigate its market. As such, the study tried to look into the risks and benefits of crypto gaming if it would be regulated by the government, and how market volatility influences the churn rate of crypto games. Method – The research used a descriptive study to determine the perception of people who are engaged in playing “Axie Infinity”. The research also used non-probability sampling using the snowball method. The only tool used to collect data was Google Forms. Furthermore, the study used Statistical Package for Social Science (SPSS) to analyze the descriptive data. Result – The results showed that most players spend their time playing Axie Infinity for about 1 to 4 hours a day. Predominantly, the return of investments for playing the game will take about 1 to 3 months. It also showed that these players agreed that there is a possible financial instability in a volatile market. With this, they have a high trust issue in terms of price manipulation, privacy and security, and its design and usability. Conclusion – Understanding the cryptocurrency market requires comprehending the perspective of the people who are engaged in a play-to-earn game, and their concerns are critical for any government actions aimed at regulating self-employed income earners playing (Non-fungible Tokens) NFT games in the Philippines. Recommendations – It is suggested that further research must be conducted to understand how self-employed Filipino income earners comprehend NFT gaming and cryptocurrency, impacting their level of interest and participation. Research Implications – Taxing NFT games without sound regulatory frameworks may result in the disarray of this alternative income source. Therefore, the government must tread carefully to avoid a market collapse or other unfavorable outcomes.